A high-viscosity acrylic adhesive for film and preparation method thereof
By using polyether sulfone crosslinked derivatives in acrylic adhesives for crosslinking polymerization, the problems of poor high temperature resistance and poor bonding properties of acrylic adhesives in the prior art are solved, and high viscosity and high temperature resistance are achieved Acrylic adhesives ensure the stability and protection of electronic products films.
Patent Information
- Application Number
- CN202411419225.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The existing acrylic adhesives have poor high temperature resistance and are not strong in bonding properties, which cannot effectively prevent the film from being thermally aging caused by heating in electronic products, such as curling, edge lifting and falling off.
Polyethersulfone crosslinking derivatives are used as crosslinking agents to carry out crosslinking polymerization under high temperature conditions to form acrylate molecular chains with high crosslinking density, and polyethersulfone molecular chains are introduced to enhance molecular stability, bind ether bonds and The combination of chemical bonds and the bonded matrix is prepared to produce a highly viscous acrylic adhesive.
It significantly improves the high temperature resistance and bonding strength of acrylic adhesives, ensuring the stability and protection effect of the film under high temperature environment.
Smart Images

Figure CN118956337B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, and in particular to a high-viscosity acrylic adhesive for films and a preparation method thereof. Background Art
[0002] In modern industry and daily life, film materials are widely used in packaging, electronics, construction, medical and other fields due to their excellent flexibility, transparency, barrier properties and lightweight characteristics. Especially in electronic products, as electronic products have been increasingly popularized in recent years, in order to prevent scratches, almost all electronic products on the market, such as mobile phones and tablets, need to be protected by films. The effective bonding between the film and the substrate cannot be separated from the support of high-performance adhesives. Among them, acrylic adhesives have become the only choice in the field of film bonding due to their excellent bonding performance, good weather resistance, environmental protection characteristics and easy processing.
[0003] Since electronic products will generate heat when in use, especially in hot outdoor environments in summer, the adhesive used for electronic protective films needs to have good heat resistance and high viscosity, otherwise thermal aging may occur, which may not only cause the film to curl and produce edge lift, affecting usability, but may also cause the film to fall off, causing electronic products to lose their protective function. However, the acrylic adhesives currently on the market have poor high heat resistance and weak bonding performance. Therefore, it is of great significance to develop an acrylic adhesive that is resistant to high temperatures and has excellent bonding performance. Summary of the invention
[0004] 1. Technical problems solved:
[0005] In view of the deficiencies in the prior art, the present invention provides a high-viscosity acrylic adhesive for thin films and a preparation method thereof.
[0006] (II) Technical solution:
[0007] A method for preparing a high-viscosity acrylic adhesive for a film, wherein the high-viscosity acrylic adhesive is prepared from the following raw materials in parts by weight:
[0008] 20-30 parts of methyl methacrylate;
[0009] 2-5 parts of butyl methacrylate;
[0010] 1-4 parts of tetrahydrofuran methacrylate;
[0011] 0.5-1.5 parts of polyethersulfone cross-linked derivative;
[0012] Initiator 0.5-1 part;
[0013] 1-2 parts of defoaming agent;
[0014] Photoinitiator 0.3-0.6 parts;
[0015] The preparation method is as follows:
[0016] The first step is to prepare a prepolymer;
[0017] First, add methyl methacrylate, butyl methacrylate, and tetrahydrofuran methacrylate to a polymerization kettle filled with nitrogen. After the addition, start stirring, wait for uniform mixing, add an initiator, and after the addition, gradually heat up to 78-82° C., keep warm for 3-5 hours under stirring conditions, then add a polyethersulfone cross-linked derivative, after the addition, continue to keep warm and stir for 9-12 hours, stop heating, and discharge the material after natural cooling to obtain a prepolymer;
[0018] The second step is to add the photoinitiator to the prepolymer. After adding, mechanically stir at a stirring rate of 500-600r / min for 10-20min. Then, add the defoamer to the prepolymer, stir evenly, and let it stand for 20-40min to obtain a high-viscosity acrylic adhesive.
[0019] As a further embodiment of the present invention, the preparation method of the polyethersulfone cross-linked derivative is as follows:
[0020] 3-[bis(glycidyloxymethyl)methoxy]-1,2-propanediol, sodium hydride and toluene are added to a polymerization kettle, followed by vacuuming, nitrogen flow, stirring, and uniform mixing. The temperature is then raised to 50-60°C and stirred for 1-2 hours. The halogen-terminated polyethersulfone is then added to the polymerization kettle. After the halogen-terminated polyethersulfone is completely dissolved, the temperature is gradually raised to 80-90°C. After stirring for 8-10 hours, the heating is stopped, and after the temperature is cooled to room temperature, the end-capping agent is added to the polymerization kettle. After the addition is completed, the mixture is stirred at room temperature for 2-4 hours. The nitrogen is removed and the material is discharged to obtain a cross-linked polyethersulfone derivative.
[0021] In the above technical scheme, sodium hydride is first used to activate the active hydroxyl groups in the structure of 3-[bis(glycidyloxymethyl)methoxy]-1,2-propylene glycol, and then continuous substitution polymerization is carried out with the halogen substituents in the halogen-terminated polyethersulfone structure under high temperature conditions to form an alternating polymer intermediate containing polyethersulfone. By controlling the amount of the two, the polymer intermediate can be hydroxyl-terminated, and then by using a capping agent to cap it, a polyethersulfone cross-linked derivative with an unsaturated olefinic substituent at the end of the structure can be obtained.
[0022] As a further embodiment of the present invention, the preparation method of the halogen-terminated polyethersulfone is as follows:
[0023] Add the hydroxy-terminated polyethersulfone to 1,4-dioxane, stir mechanically to form a uniform mixed solution, then add the halogenating agent to the mixed solution, introduce nitrogen for protection, add a catalyst for catalysis, and then gradually control the temperature to 70-80°C, maintain for 3-5 hours, evaporate and remove the solvent, stop heating, cool and discharge the material, and then obtain the halogen-terminated polyethersulfone.
[0024] As a further embodiment of the present invention, the number average molecular weight of the hydroxy-terminated polyethersulfone is 5,000.
[0025] As a further embodiment of the present invention, the halogenating agent is 2-chloroethyl isocyanate or 3-chloropropyl isocyanate.
[0026] As a further embodiment of the present invention, the catalyst is any one of dibutyltin dilaurate, dibutyltin diacetate or dioctyltin dilaurate.
[0027] As a further embodiment of the present invention, the mass ratio of the 3-[bis(glycidyloxymethyl)methoxy]-1,2-propylene glycol to the halogen-terminated polyethersulfone is 1:15-16.
[0028] As a further embodiment of the present invention, the end-capping agent is methacryloyl chloride or acryloyl chloride.
[0029] In the above technical scheme, a catalyst is first used to catalyze the isocyanate group in the halogenation reagent structure to undergo an amine esterification reaction with the substituted hydroxyl group in the terminal hydroxyl polyether sulfone structure, thereby achieving halogen modification of the polyether sulfone and obtaining a halogen-terminated polyether sulfone.
[0030] As a further embodiment of the present invention, the initiator is azobisisobutyronitrile or azobisisoheptanenitrile; the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone or 1-hydroxycyclohexyl phenyl ketone.
[0031] A high-viscosity acrylic adhesive for thin films is prepared by adopting the preparation method.
[0032] 3. Beneficial technical effects:
[0033] The present invention realizes cross-linking polymerization of acrylic acid molecular chains by preparing a cross-linked polyethersulfone derivative containing a polyethersulfone alternating structure as a cross-linking agent. On the one hand, the cross-linking density of the acrylic acid ester molecular chain in this structure is higher, the cohesive force is greater, and a higher bonding strength can be exhibited. On the other hand, during the polymerization process, the polyethersulfone molecular chain is introduced into the main chain of the acrylic acid molecular chain. Since the polyethersulfone molecular chain contains a large number of continuous rigid benzene ring structures, the introduction of this structure can improve the stability of the acrylic acid molecular chain, so that it needs to absorb more energy when thermally decomposed, thereby effectively enhancing the high temperature resistance of the acrylic acid adhesive. In addition, the cross-linked polyethersulfone derivative also contains an ether bond generated by a substitution reaction, and an epoxy group, wherein the ether bond can generate a hydrogen bond with the adhered substrate, and the epoxy group can be chemically bonded with the adhered substrate, so that the prepared acrylic acid adhesive exhibits excellent bonding performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0035] Figure 1 This is the FT-IR graph of polyethersulfone cross-linked derivatives. DETAILED DESCRIPTION
[0036] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. Preferred embodiments of the present invention are given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0037] Preparation Example 1:
[0038] Preparation of cross-linked polyethersulfone derivatives:
[0039] Step 1: add 3.2 g of hydroxy-terminated polyethersulfone with a number average molecular weight of 5000 to 1,4-dioxane, stir mechanically to form a mixed solution, then add 0.15 g of 2-chloroethyl isocyanate to the mixed solution, introduce nitrogen for protection, add 0.01 g of dibutyltin dilaurate for catalysis, and then gradually control the temperature to 75°C, maintain for 4 hours, evaporate and remove the solvent, stop heating, cool and discharge, and obtain halogen-terminated polyethersulfone;
[0040] Step 2: Add 0.5 g of 3-[bis(glycidyloxymethyl)methoxy]-1,2-propanediol, 0.1 g of sodium hydride and toluene to the polymerization kettle, then evacuate, pass nitrogen, start stirring, mix evenly, then raise the temperature to 55°C, stir for 2 hours, then add 7.5 g of halogen-terminated polyethersulfone to the polymerization kettle, after it is completely dissolved, gradually raise the temperature to 85°C, keep stirring for 10 hours, stop heating, cool to room temperature, then add methacryloyl chloride to the polymerization kettle, after adding, stir at room temperature for 3 hours, remove nitrogen, discharge, and obtain a polyethersulfone cross-linked derivative.
[0041] The cross-linked polyethersulfone derivative was made into potassium bromide tablets and subjected to infrared testing. Figure 1 This is the FT-IR image of the cross-linked polyethersulfone derivative, where 3090 cm -1 and 3059cm -1 The characteristic carbon-hydrogen stretching vibration absorption peak of the benzene ring skeleton appeared at 3012cm -1 The characteristic stretching vibration absorption peak of unsaturated carbon-carbon double bond appears at 1748 cm -1 The C=O characteristic absorption peak of the ester group appeared at 1682 cm -1 The characteristic absorption peak of C=O in the amine ester group appeared at 1039cm -1 The characteristic stretching vibration absorption peak of ether bond appeared at 901cm -1 The characteristic absorption peak of epoxy group appeared at
[0042] Embodiment 1:
[0043] A high-viscosity acrylic adhesive for film is prepared from the following raw materials in parts by weight:
[0044] 20 parts of methyl methacrylate;
[0045] 2 parts of butyl methacrylate;
[0046] 1 part of tetrahydrofuran methacrylate;
[0047] 0.5 parts of polyethersulfone cross-linked derivative;
[0048] 0.5 parts of azobisisoheptanonitrile;
[0049] Defoaming agent BYK-1790 1 part;
[0050] 2-Hydroxy-2-methyl-1-phenyl-1-propanone 0.3 parts;
[0051] The preparation method of the high-viscosity acrylic adhesive is as follows:
[0052] The first step is to prepare a prepolymer;
[0053] First, methyl methacrylate, butyl methacrylate and tetrahydrofuran methacrylate were added to a polymerization kettle filled with nitrogen. After the addition, stirring was started. After the mixture was evenly mixed, azobisisoheptanenitrile was added. After the addition was completed, the temperature was gradually raised to 78° C. and kept warm for 5 h under stirring. Then, a polyethersulfone cross-linked derivative was added. After the addition was completed, the temperature was kept warm and stirred for 12 h. The heating was stopped, and the mixture was discharged after natural cooling to obtain a prepolymer.
[0054] The second step is to add 2-hydroxy-2-methyl-1-phenyl-1-propanone to the prepolymer. After the addition, mechanically stir at a stirring rate of 500r / min for 10 minutes. Then, add the defoaming agent BYK-1790 to the prepolymer, stir evenly, and let it stand for 40 minutes to obtain a high-viscosity acrylic adhesive.
[0055] The preparation method of the cross-linked polyethersulfone derivative is shown in Preparation Example 1, and the same is true for the following.
[0056] Embodiment 2:
[0057] A high-viscosity acrylic adhesive for film is prepared from the following raw materials in parts by weight:
[0058] 28 parts of methyl methacrylate;
[0059] 4 parts of butyl methacrylate;
[0060] 3 parts of tetrahydrofuran methacrylate;
[0061] 1 part of polyethersulfone cross-linked derivative;
[0062] 0.8 parts of azobisisobutyronitrile;
[0063] Defoamer BYK-1790 1.5 parts;
[0064] 0.5 part of 1-hydroxycyclohexyl phenyl ketone;
[0065] The preparation method of the high-viscosity acrylic adhesive is as follows:
[0066] The first step is to prepare a prepolymer;
[0067] First, methyl methacrylate, butyl methacrylate and tetrahydrofuran methacrylate were added to a polymerization kettle filled with nitrogen. After the addition, stirring was started. After the mixture was evenly mixed, azobisisobutyronitrile was added. After the addition was completed, the temperature was gradually raised to 80° C. and kept warm for 4 hours under stirring. Then, a polyethersulfone cross-linked derivative was added. After the addition was completed, the temperature was kept warm and stirred for 10 hours. The heating was stopped, and the mixture was discharged after natural cooling to obtain a prepolymer.
[0068] The second step is to add 1-hydroxycyclohexyl phenyl ketone to the prepolymer. After the addition, mechanically stir at a stirring rate of 600r / min for 15 minutes. Then, add the defoamer BYK-1790 to the prepolymer, stir evenly, and let it stand for 30 minutes to obtain a high-viscosity acrylic adhesive.
[0069] Embodiment 3:
[0070] A high-viscosity acrylic adhesive for film is prepared from the following raw materials in parts by weight:
[0071] 30 parts of methyl methacrylate;
[0072] Butyl methacrylate 5 parts;
[0073] 4 parts of tetrahydrofuran methacrylate;
[0074] 1.5 parts of polyethersulfone cross-linked derivative;
[0075] 1 part of azobisisobutyronitrile;
[0076] Defoamer BYK-1790 2 parts;
[0077] 0.6 part of 1-hydroxycyclohexyl phenyl ketone;
[0078] The preparation method of the high-viscosity acrylic adhesive is as follows:
[0079] The first step is to prepare a prepolymer;
[0080] First, methyl methacrylate, butyl methacrylate and tetrahydrofuran methacrylate were added to a polymerization kettle filled with nitrogen. After the addition, stirring was started. After the mixture was evenly mixed, azobisisobutyronitrile was added. After the addition was completed, the temperature was gradually raised to 82° C. and kept warm for 3 h under stirring. Then, a cross-linked polyethersulfone derivative was added. After the addition was completed, the temperature was kept warm and stirred for 9 h. The heating was stopped, and the mixture was discharged after natural cooling to obtain a prepolymer.
[0081] The second step is to add 1-hydroxycyclohexyl phenyl ketone to the prepolymer. After the addition, mechanically stir at a stirring rate of 600r / min for 20 minutes. Then, add the defoaming agent BYK-1790 to the prepolymer, stir evenly, and let it stand for 40 minutes to obtain a high-viscosity acrylic adhesive.
[0082] Comparative Example 1:
[0083] An acrylic adhesive for a film is prepared from the following raw materials in parts by weight:
[0084] 28 parts of methyl methacrylate;
[0085] 4 parts of butyl methacrylate;
[0086] 3 parts of tetrahydrofuran methacrylate;
[0087] 0.8 parts of azobisisobutyronitrile;
[0088] Defoamer BYK-1790 1.5 parts;
[0089] 0.5 part of 1-hydroxycyclohexyl phenyl ketone;
[0090] The preparation method of the acrylic adhesive is as follows:
[0091] The first step is to prepare a prepolymer;
[0092] First, add methyl methacrylate, butyl methacrylate and tetrahydrofuran methacrylate into a polymerization kettle filled with nitrogen. After the addition, start stirring. After mixing evenly, add azobisisobutyronitrile. After the addition, gradually heat to 80° C., keep warm for 10 hours under stirring, stop heating, cool naturally and then discharge to obtain a prepolymer.
[0093] The second step is to add 1-hydroxycyclohexyl phenyl ketone to the prepolymer. After the addition, mechanically stir at a stirring rate of 600r / min for 15 minutes. Then, add the defoaming agent BYK-1790 to the prepolymer, stir evenly, and let it stand for 30 minutes to obtain the acrylic adhesive.
[0094] Test example:
[0095] Using polyimide film as the substrate, the acrylic adhesives in the embodiment and the comparative example were coated on the surface of the substrate with the same specifications, and then the release layer was covered on the adhesive coating layer. 2 The substrate was irradiated with a mercury lamp to completely cure it, and the sample was attached to the glass surface, and then a 180° peel strength test was performed. The test method refers to the standard GB / T2791-1995. After the test, the samples of the same specifications were placed in an environment with a temperature of 80°C for 3 days and then taken out to observe the phenomenon and test the peel strength again. The test results are shown in the following table:
[0096]
[0097] According to the test results, the acrylic adhesive prepared by using the cross-linked polyethersulfone derivative prepared in Preparation Example 1 of the present invention as a raw material has better bonding performance and excellent high temperature resistance.
[0098] Based on the ideal embodiment of the present invention, through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a high-viscosity acrylic adhesive for a film, characterized in that: The high-viscosity acrylic adhesive is made of the following raw materials in parts by weight: 20-30 parts of methyl methacrylate; 2-5 parts of butyl methacrylate; 1-4 parts of tetrahydrofuran methacrylate; 0.5-1.5 parts of polyethersulfone cross-linked derivative; Initiator 0.5-1 part; 1-2 parts of defoaming agent; Photoinitiator 0.3-0.6 parts; The preparation method is as follows: Step 1: Preparation of prepolymer First, add methyl methacrylate, butyl methacrylate, and tetrahydrofuran methacrylate to a polymerization kettle filled with nitrogen. After the addition, start stirring, wait for uniform mixing, add an initiator, and after the addition, gradually heat up to 78-82° C., keep warm for 3-5 hours under stirring conditions, then add a polyethersulfone cross-linked derivative, after the addition, continue to keep warm and stir for 9-12 hours, stop heating, and discharge the material after natural cooling to obtain a prepolymer; The second step is to add the photoinitiator to the prepolymer, and then mechanically stir it at a stirring rate of 500-600r / min for 10-20min, then add the defoamer to the prepolymer, stir evenly, and let it stand for 20-40min to obtain a high-viscosity acrylic adhesive; The preparation method of the polyethersulfone cross-linked derivative is as follows: 3-[bis(glycidyloxymethyl)methoxy]-1,2-propanediol, sodium hydride and toluene are added to a polymerization kettle, followed by vacuuming, nitrogen flow, stirring, and uniform mixing. The temperature is then raised to 50-60°C and stirred for 1-2 hours. The halogen-terminated polyethersulfone is then added to the polymerization kettle. After the halogen-terminated polyethersulfone is completely dissolved, the temperature is gradually raised to 80-90°C. After stirring for 8-10 hours, the heating is stopped, and after the temperature is cooled to room temperature, the end-capping agent is added to the polymerization kettle. After the addition is completed, the mixture is stirred at room temperature for 2-4 hours. The nitrogen is removed and the material is discharged to obtain a cross-linked polyethersulfone derivative.
2. The method for preparing a high-viscosity acrylic adhesive for a film according to claim 1, characterized in that: The preparation method of the halogen-terminated polyether sulfone is as follows: Add the hydroxy-terminated polyethersulfone to 1,4-dioxane, stir mechanically to form a uniform mixed solution, then add the halogenating agent to the mixed solution, introduce nitrogen for protection, add a catalyst for catalysis, and then gradually control the temperature to 70-80°C, maintain for 3-5 hours, evaporate and remove the solvent, stop heating, cool and discharge the material, and then obtain the halogen-terminated polyethersulfone.
3. The method for preparing a high-viscosity acrylic adhesive for a film according to claim 2, characterized in that: The number average molecular weight of the hydroxy-terminated polyethersulfone is 5,000.
4. The method for preparing a high-viscosity acrylic adhesive for a film according to claim 2, characterized in that: The halogenating agent is 2-chloroethyl isocyanate or 3-chloropropyl isocyanate.
5. The method for preparing a high-viscosity acrylic adhesive for a film according to claim 2, characterized in that: The catalyst is any one of dibutyltin dilaurate, dibutyltin diacetate or dioctyltin dilaurate.
6. The method for preparing a high-viscosity acrylic adhesive for a film according to claim 1, characterized in that: The mass ratio of the 3-[bis(glycidyloxymethyl)methoxy]-1,2-propylene glycol to the halogen-terminated polyethersulfone is 1:15-16.
7. The method for preparing a high-viscosity acrylic adhesive for a film according to claim 1, characterized in that: The end-capping agent is methacryloyl chloride or acryloyl chloride.
8. The method for preparing a high-viscosity acrylic adhesive for a film according to claim 1, characterized in that: The initiator is azobisisobutyronitrile or azobisisoheptanenitrile; the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone or 1-hydroxycyclohexyl phenyl ketone.
9. A high-viscosity acrylic adhesive for film, characterized in that: The method is prepared according to claim 1.
Citation Information
Patent Citations
High-viscosity pressure-sensitive adhesive, production method of high-viscosity pressure-sensitive adhesive and adhesive tape
CN110628366A
Ester-terminated polyethersulfone block copolymer as well as preparation method and application thereof
CN118126268A